HRM Practices, Organizational Citizenship Behaviour, and Performance: A Multi‐Level Analysis - Snape, Ed; Redman, Tom (Journal of Management Studies, 2010)
abstractWe examine the relationship between HRM practices, conceptualized at the workplace level, and individual employee attitudes and behaviour. We focus on two possible explanations for the relationship: social exchange and job influence/employee discretion. Findings from a study of employees in North‐East England suggest that there is a positive impact of HRM practices on organizational citizenship behaviour, through an effect on perceived job influence/discretion. There was no such effect for perceived organizational support. These findings provide support for a job influence and opportunity explanation of HRM effects on employee attitudes and behaviour.